PENGEMBANGAN DAN IMPLEMENTASI MEDIA PEMBELAJARAN ANIMASI EDUKATIF BERBASIS CANVA PADA TEMA MENJELAJAHI BUMI DAN ANTARIKSA - Ariesta; Dianita Tri Lestari; Hedin Hendratarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was prompted by issues found within elementary schools regarding the limited integration of digital tools in science education, which often leads to students being passive and less engaged in learning. Therefore, the author developed a Canva-based teaching aid to simplify the delivery of information, particularly for abstract topics. The aim of this study is to create and evaluate the feasibility of an educational resource in the form of an animated video with the theme Exploring Earth and Antarctica. The methodology used in this study is the Research and Development (R&D) method, which includes needs analysis, product design, media creation, validation by media experts, and subject matter experts. The research data consists of assessments from three subject matter experts who are experienced educators in the field and three media experts who are experienced in animation. A five-point Likert scale questionnaire was used The results of this research indicate that the subject matter experts assessed the Canva-produced animated teaching materials to have a subject matter expert feasibility rate of 97.78%, and are thus deemed very feasible. The media experts also gave an assessment of 90%, and are thus deemed very feasible. As a result, the Canva-based animated teaching materials are considered appropriate for use in science education and have the potential to increase student interest and understanding. Future studies should incorporate field tests to thoroughly assess how this material affects student learning outcomes in a real-world setting.